Using moral and epistemological reasoning as predictors of prejudice. - Glover, Rebecca J. (Journal of Social Psychology, 1994)
A study was conducted to examine the relative importance that an individual gives to principled moral reasoning and to relativism, with respect to positive and negative attitudes toward minorities and to traditional and modern forms of racism. Subjects were 207 individuals from the University of Arkansas, Fayetteville. The results of regression analyses revealed that those students who were more humanitarian-egalitarian in their outlook, who were less supportive of the Protestant ethic, who possessed a high level of education, and who used a high percentage of relativism in their decision making were more likely to have positive attitudes toward minorities than those individuals not possessing such characteristics. Only age was a predictor of negative attitudes toward minorities. These results help to give a rationale for further examination of the relationship between moral and epistemological reasoning and for implementation of moral education programs as a way to reduce negative racial attitudes.